2016
DOI: 10.1002/mnfr.201500686
|View full text |Cite
|
Sign up to set email alerts
|

Circulating triglycerides and bile acids are reduced by a soluble wheat arabinoxylan via modulation of bile concentration and lipid digestion rates in a pig model

Abstract: The results suggest that AXRF reduced the levels of circulating BAs which slowed down the digestion of TAG and absorption of free fatty acids, with consequent reduction in blood TAG. Reduction in circulating bile acids by arabinoxylan causes reduction in lipids digestion and absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 42 publications
5
37
1
Order By: Relevance
“…The digesta and blood results give more information on the reabsorption of the BAs from different small intestine sites into the blood circulation. The significant decreases in TBA and the primary BAs CDCA and HCA in the Mid Jeju, Ter Ileu, and JV suggest that there were lower levels of BAs circulating in the BG diet group and are in accordance with a recent report that showed that a wheat AX-enriched fraction supplementation of the diet of a pig model reduced the concentrations of circulating BAs (24). There was a large drop in BA concentration between the Ter Ileu and cecum of control pigs, but there was no change between these sites in pigs fed the BG diet.…”
Section: Bassupporting
confidence: 90%
See 3 more Smart Citations
“…The digesta and blood results give more information on the reabsorption of the BAs from different small intestine sites into the blood circulation. The significant decreases in TBA and the primary BAs CDCA and HCA in the Mid Jeju, Ter Ileu, and JV suggest that there were lower levels of BAs circulating in the BG diet group and are in accordance with a recent report that showed that a wheat AX-enriched fraction supplementation of the diet of a pig model reduced the concentrations of circulating BAs (24). There was a large drop in BA concentration between the Ter Ileu and cecum of control pigs, but there was no change between these sites in pigs fed the BG diet.…”
Section: Bassupporting
confidence: 90%
“…As discussed in Gunness et al . (24), diet seems to be an important factor in the modulation of circulating BAs. Indeed, in both experiments, without SDFs in the diets, the BA profiles were different: HDCA was more abundant with the Western‐style diet (24), and with the present diet containing 2% cholesterol as animal lipids, CDCA was more abundant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…used an intrauterine growth restriction (IUGR) pig model to explore the influence of postnatal nutrition restriction on the oxidative status of neonates, and the study revealed that postnatal nutrition restriction induced compromised antioxidant defense systems in IUGR pigs . It was demonstrated that a soluble wheat arabinoxylan‐rich fraction (AXRF) decreased the concentrations of triglycerides and bile acids (BAs) in serum, which in turn retarded the metabolism of triacylglycerol and absorption of free fatty acids in pig models . High‐fat/low‐fiber or low‐fat/high‐fiber diets reported to influence intestinal microbiota and microbial metabolites, further suggesting that pigs are a promising model system to study diet–gut microbiota interactions in humans …”
Section: Common Models Used In Nutritional Studiesmentioning
confidence: 99%